\[ \left (y(x)^2+1\right ) y''(x)-3 y(x) y'(x)^2=0 \] ✓ Mathematica : cpu = 0.155657 (sec), leaf count = 93
\[\left \{\left \{y(x)\to -\frac {i c_1 (c_2+x)}{\sqrt {c_1{}^2 x^2+2 c_2 c_1{}^2 x+c_2{}^2 c_1{}^2-1}}\right \},\left \{y(x)\to \frac {i c_1 (c_2+x)}{\sqrt {c_1{}^2 x^2+2 c_2 c_1{}^2 x+c_2{}^2 c_1{}^2-1}}\right \}\right \}\] ✓ Maple : cpu = 0.04 (sec), leaf count = 33
\[ \left \{ y \left ( x \right ) =\sqrt {- \left ( {{\it \_C1}}^{2}{x}^{2}+2\,{\it \_C1}\,{\it \_C2}\,x+{{\it \_C2}}^{2}-1 \right ) ^{-1}} \left ( {\it \_C1}\,x+{\it \_C2} \right ) \right \} \]